Potencial fisiológico das sementes de chia em função da coloração do tegumento. - Rios Filho, Sérgio Luiz Ferreira (2018)
The use of high quality seeds is a very important factor for the sucess of propagation and production of vigorous seedling, haveing as paramenter the test of germination and vigor tests for the evaluation of the physiological potential of the seeds. Thus, the objective of this research was to evaluate the physiological potential of the chia seeds as a function of tegument color. The experiment was conducted in the Laboratory of Analysis of Seeds, Federal University of Ceará. Two batches of chia were used, in which a seed classification was performed as a function of the tegument coloration in: dark , intermediate and light seeds. In addition , the tests were also performed with seeds without any separation, being classified as the mixture. For the initial characterization of the seeds, the water content, the dry matter mass of the seeds and the weight of the thousand seeds were determined. The seeds were submitted to germination test, maintained in B.O.D under 25 °C for 14 days, and the resulted expressed as mean percentage of normal seedlings for each treatment. The first germination count was performed on the seventh day of the germination test. After the germination test, seedling dry matter mass was determined on day fourteenth. Normal seedlings were dried in na air cirulation oven at 65 °C for the 24 and the results were expressed in miligrams per seedlings. The emergency test was performed under greenhouse conditions under controlled conditions and was evaluated on the 14 th day after planting. Daily counts were calculated for the calculation of the emergency speed index. A completely randomized design was used. The data were submitted to analisys of variance and their means were compared in a Tukey test at 5%. It was verified that there was no significant difference between the treatments for the two batches analyzed. The percentage of germination observed for lot 1 was on average 59% and 82% for lot 2. The dry matter mass for lot 1 was on average 0,0215g and 0,027 for lot 2. With this, it is concluded that the seeds of different tegument stains have similar quality. Thus, it is not necessary to perform the classification of the seeds in function of the color of the tegument as a step of the beneficiation process.